Off-Pump Debranching and Thoracic Endovascular Aortic Repair for Aortic Arch Pathology. Issue 3 (May 2015) - Ghazy, Tamer; Mashhour, Ahmed; Schmidt, Torsten; Mahlmann, Adrian; Ouda, Ahmed; Florek, Hans-Joachim; Matschke, Klaus; Kappert, Utz
Abstract : Objective: This study aimed to simplify an until-now complex procedure for the treatment of proximal aortic arch pathology (zones 0 and 1), where a deep hypothermic circulatory arrest even with selective cerebral perfusion is still a high-risk procedure with accompanying splanchnic and spinal cord ischemia. Methods: From June 2012 until March 2013, 106 patients underwent aortic surgery in our institution, of whom, 20 patients underwent aortic arch surgery. Of the 20 patients, 7 with multiple comorbidities and a high operative risk and no other indication for a cardiopulmonary bypass were selected to undergo an off-pump aortic arch debranching and thoracic endovascular aortic repair: 4 patients had chronic dissections, and 3 patients had arch aneurysms. The procedure was performed through median sternotomy. The supraaortic branches were rerouted to the ascending aorta, and this process was followed by thoracic endovascular aortic repair of the aortic arch and proximal descending aorta. Transaortic antegrade stenting was performed in 5 cases. Cerebral protection and perfusion monitoring were achieved by biradial pressure monitoring, electroencephalogram, and online transcranial duplex sonography. The preoperative, operative, and postoperative data were collected and analyzed retrospectively. Results: All procedures were successful. There were no conversions to cardiopulmonary bypass support. The mean operative time was 184 ± 24 minutes. Postoperatively, there was 1 rethoracotomy for bleeding and 1 cerebrovascular insult. The 30-day mortality was 1 patient. Conclusions: Off-pump aortic debranching with arch stenting is a reproducible procedure that could be favorable in certain situations, such as in patients with a higher operative risk profile, thereby reducing the risks associated with deep hypothermic circulatory arrest and also yielding favorable outcomes, even in an older patient cohort with more comorbidities.